2021
DOI: 10.3390/su13179862
|View full text |Cite
|
Sign up to set email alerts
|

Tri-tert-butyl(n-alkyl)phosphonium Ionic Liquids: Structure, Properties and Application as Hybrid Catalyst Nanomaterials

Abstract: A series of sterically hindered tri-tert-butyl(n-alkyl)phosphonium salts (n-CnH2n+1 with n = 1, 3, 5, 7, 9, 11, 13, 15, 17) was synthesized and systematically studied by 1H, 13C, 31P NMR spectroscopy, ESI-MS, single-crystal X-ray diffraction analysis and melting point measurement. Formation and stabilization palladium nanoparticles (PdNPs) were used to characterize the phosphonium ionic liquid (PIL) nanoscale interaction ability. The colloidal Pd in the PIL systems was described with TEM and DLS analyses and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…In the current work, we systematically studied the influence of the oxygen-containing substituents in cation on the physical-chemical properties of oxy-QPSs. The obtained trends were compared with the previously reported alkyl-substituted analog [28,29]. Some features of the crystal packing of oxy-QPSs were discussed.…”
Section: Introductionmentioning
confidence: 96%
“…In the current work, we systematically studied the influence of the oxygen-containing substituents in cation on the physical-chemical properties of oxy-QPSs. The obtained trends were compared with the previously reported alkyl-substituted analog [28,29]. Some features of the crystal packing of oxy-QPSs were discussed.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, the applications of PhILs are diverse and in recent years the areas of their use have been presented as catalysts for the cycloaddition of carbon dioxide to epoxides [23], anticorrosive additives for pigments in epoxy coatings [24] or in the extraction of gold from thiosulfate solutions [25]. Moreover, many applications of this group of compounds in catalysis and carbon dioxide absorption are known [26,27]. In contrast, ionic liquids containing charge-free phosphorus in their structure are simpler to synthesize and, in most cases, do not require special conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the structures of alkyl derivatives vary depending on the chain length. Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length.…”
Section: Introductionmentioning
confidence: 99%